2020
DOI: 10.47197/retos.v1i40.82863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of body composition and its relationship with physical fitness in professional soccer players at the beginning of pre-season (Evaluación de la composición corporal y su relación com la aptitud física em futebolistas professionales al inicio de

Abstract: The aim of the study was to compare the players characteristics and physical fitness parameters according to playing positions and to identify the relation between body composition and physical fitness in professional soccer players at the beginning of the preparation period. Sixteen professional soccer players participated in this study. Body composition was evaluated by air displacement plethysmography instrumentation (BOD POD®) and physical fitness with specific tests: Running Anaerobic Sprint Test (RAST), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
(23 reference statements)
0
1
1
2
Order By: Relevance
“…It should be noted that most previous interventions in adolescents analyzed the changes produced in cardiorespiratory fitness (Badawy & Kuhns, 2017 ; Goodyear et al, 2021 ), a few studies assessed changes in capacities such as muscular endurance (Schoeppe et al, 2016 ), but no previous research with mobile applications is known to have analyzed the modifications produced in jump height. The differences obtained in the present study could be due to the increase in muscle mass and corrected thigh girth observed in the intervention group, since they are factors that favor the production of lower limb strength (De Almeida-Neto et al, 2021 ; Figueiredo et al, 2020 ; Vuk et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 51%
“…It should be noted that most previous interventions in adolescents analyzed the changes produced in cardiorespiratory fitness (Badawy & Kuhns, 2017 ; Goodyear et al, 2021 ), a few studies assessed changes in capacities such as muscular endurance (Schoeppe et al, 2016 ), but no previous research with mobile applications is known to have analyzed the modifications produced in jump height. The differences obtained in the present study could be due to the increase in muscle mass and corrected thigh girth observed in the intervention group, since they are factors that favor the production of lower limb strength (De Almeida-Neto et al, 2021 ; Figueiredo et al, 2020 ; Vuk et al, 2015 ).…”
Section: Discussioncontrasting
confidence: 51%
“…Silvestre et al detected a statistically significant relationship between body composition and vertical jump, while Anwar and Noohu reported a moderately significant negative correlation between body fat percentage and vertical jump in university-educated football players [26,21]. Esco et al found a strong negative correlation between the body fat percentage of football players and vertical jump, and Figueiredo et al observed a negative relationship between body fat percentage and jumping performance in professional football players [27,28]. A study by Atakan et al concluded that jumping performance was negatively affected by an increase in body fat percentage in football players [29].…”
Section: Discussionmentioning
confidence: 99%
“…Estudios previos realizados con futbolistas de diferentes categorías (González et al, 2023;Figueiredo et al, 2021;Gurrola et al, 2021;Ruíz, et al, 2019;Gorla, 2019) destacan la relevante importancia en la identificación del perfil de somatotipo, incluso en diferentes posiciones de juego, y la Composición Corporal en diferentes períodos de entrenamiento, como factores determinantes del rendimiento deportivo.…”
Section: Discussionunclassified